Orthopedic Calf Cast Using Antioxidative FS3200PA Nylon 3D Printing: Design And Optimization - Hussin, Mohamed Saiful Firdaus; Omar, Mohammad Rafi; Azlan, Khairul Azri; Azahar, Arman Hadi; Ismail, Zulkefli; Rosli, Fatin Farhana (Asian Research Publishing Network, 2019)
Current cast designs such as heavy plaster cast come up with many disadvantages to patient like discomfort and itchy skin. Most of the hospitals in Malaysia are still using traditional custom made cast which is made by paris and mold that cannot be recycled. The objectives of this project were to design custom fit orthopedic cast and to optimize the weight of cast that used material of FS3200PA Nylon powder that has generally good anti-oxidative properties and not harmful to health. Computer Aided Design (CAD) software and Finite Element Analysis (FEA) computer software were used to design and optimize the shape and geometry of calf cast. T-Scan LV system is used for scanning process. The load applied for simulation are 981 N, 784.8 N, and 588.6 and the thickness varies between 1 mm, 2 mm and 3 mm. Safety factor of 1.0 ≤ s. f ≤ 3.0 is considered in selecting the acceptable combination. Fabrication of the cast had been made by used the Farsoon SS 402P laser sintering system. Through optimization and analysis, three combinations of the models are proven to be a safe-to-use model.